Comprehensive analysis of dysregulated circular RNAs and construction of a ceRNA network involved in the pathology of Alzheimer’s disease in a 5 × FAD mouse model - Sun, Ting; Zeng, Li; Cai, Zhongdi; Liu, Qingshan; Li, Zhuorong; Liu, Rui (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) causes a decline in cognitive function that poses a significant hazard to human health. However, the exact pathogenesis of AD and effective treatment have both proven elusive. Circular RNAs (circRNAs), which were initially deemed as meaningless non-coding RNAs, have been shown to participate in a variety of physiological and pathological processes. However, the variations and characteristics of circRNAs are not fairly well understood during the occurrence and development of AD. In this study, we performed RNA sequencing analyses, identified circRNA expression profiles, and explored the circRNA-associated competing endogenous RNA (ceRNA) relationship in the hippocampus of five familial AD (5×FAD) mice with cognitive dysfunction. The RNA sequencing results identified 34 dysregulated circRNAs in the hippocampus of 5×FAD mice, including 17 upregulated and 17 downregulated circRNAs. The circRNA-miRNA interaction network for the dysregulated circRNAs was generated, including 34 circRNAs and 711 miRNAs. Next, 2067 mRNAs potentially modulated by upregulated circRNA-interacting miRNAs and 2297 mRNAs potentially modulated by downregulated circRNA-interacting miRNAs were identified. Pathway enrichment analyses revealed that the circRNA-miRNA-mRNA network modulated AD development via multiple pathways, such as axon guidance, mitogen-activated protein kinase, and neurotrophin. The associated biological processes were mainly related to neuron projection development, cell morphogenesis, and head development. Their corresponding distributions were especially high in the axon, postsynapse, and neuronal body. We constructed a ceRNA network that included five circRNAs, four miRNAs, and 188 mRNAs. In this network, the differential expressions of three circRNAs (circRNA04655, circRNA00723, and circRNA01891), two miRNAs (miR-3470b and miR-6240), and 13 mRNAs (Vgll3, Nhsl2, Rab7, Tardbp, Vps33b, Fam107a, Tacr1, Ankrd40, Creb1, Snap23, Csnk1a1, Bmi1, and Bfar) in the hippocampus of 5×FAD mice using qRT-PCR analyses were consistent with the RNA sequencing results. Another one circRNAs (circRNA00747) and two mRNAs (Zfp37 and Polr1e) had similar expression trends to the sequencing data, while circRNA03723 and Mapk10 had deviated expression trends to the sequencing data. In conclusion, our study uncovered dysregulated circRNA expression profiles in the hippocampus of 5×FAD mice, stretched comprehension of ceRNA biology, investigated potential role of this ceRNA network in pathogenesis and progression, and identified potential biomarkers and therapeutic targets for AD.